Assessment of the School Management, Library, and Media System for Student Efficiency in Nigerian Higher Education Institution - Lasisi , Abass Ayodele; Adamu , Alkali Usman (Kashere Journal of Education, 2025)
Linking the School Management, Library, and Media System in higher education institutions (HEIs) has shown that collective action is required by institutional administrators. The more the school management improves, the higher the student efficiency in higher education Institutions (HEI), through libraries with improved media systems. Descriptive Survey design was based on the simple random sampling technique on 241 respondents among 300 level of federal university of Kashere undergraduate students with the use of the School Management, Library, and Media System for Student Efficiency (SMLMS) Questionnaire to examine the ‘levels of efficiency of School Management, Library, and Media System for student efficiency in HEI’. And is there any relationship among School Management, Library, and Media System for student efficiency in HEIs? The study has shown that there is a link between School Management, and Library while Media System in educational institutions need to move from traditional approaches to modern modes in order to create a supportive, comprehensive, and effective teaching-learning environment. And it has shown that the more school management is involved, the more improvement there is in the School Library and School Media System. Thus, the present study suggested and recommended that School Management, Library, and Media Systemshould emulate counterparts and collaborate with the ICT center for student efficiency